The wrestler [videorecording (DVD)] - Aronofsky, Darren; Rourke, Mickey; Tomei, Marisa; Wood, Evan Rachel, 1987- (20th Century Fox Home Entertainment, 2009)
Back in the late '80s, Randy 'The Ram' Robinson was a headlining professional wrestler. Now, decades past his prime, he barely gets by working small wrestling shows in VFW halls and as a part-time grocery store employee. He faces health problems that may end his wrestling career and is attempting to come to terms with his life outside the ring. He wants to reconcile with the daughter he abandoned in childhood and begins a relationship with a stripper. He struggles with his new life and an offer of a high-profile rematch with his 1980s arch-nemesis, 'The Ayatollah,' which might just be his ticket back to stardom.